Minimally invasive surgery for ovarian endometriosis as a mean of improving fertility: Cystectomy vs. CO2 fiber laser ablation what do we know so far? - Candiani, Massimo; Ottolina, Jessica; Salmeri, Noemi; D’Alessandro, Sara; Tandoi, Iacopo; Bartiromo, Ludovica; Schimberni, Matteo; Ferrari, Stefano; Villanacci, Roberta (Frontiers in Surgery, 2023)
Minimally invasive surgery emerged in the 1980s as a safe and effective technique which requires smaller incisions and, usually, a shorter hospital stay compared to traditional surgery. Since then, minimally invasive surgery has expanded in many surgical specialties. One of its newest application in gynecology stands in the infertility management of young women with unexplained infertility or suspected endometriosis. In selected patients, laparoscopy allows to diagnose and treat the disease aiming to increase at best the chances of spontaneous pregnancy or trough assisted reproductive technology. Nowadays, minimally invasive surgical approach of ovarian endometriosis consists of either laparoscopic cystectomy or ablative techniques such as laparoscopic CO2 fiber laser vaporization. Although cystectomy represents the gold standard according to the latest Cochrane review, some endometriosis experts are worried about its detrimental effect on healthy ovarian parenchyma and suggest preferring a less aggressive approach such as CO2 fiber laser vaporization. The aim of this review is to give an overview of the available evidences about the impact of the two surgical procedures on ovarian reserve markers and pregnancy outcome.